Comprehensive special acrobatic training in pylon sports - N.A. Kasatkina; L.I. Kostyunina; A.F. Charykova; A.S. Egorova (Theory and Practice of Physical Culture, 2023)
Objective of the study was to improve the quality of performing acrobatic elements of various structures in pylon sports in girls aged 12-14 years. Methods and structure of the study. Analysis and generalization of scientific and methodological literature, pedagogical experiment, testing, method of expert assessments, statistical data processing. The pedagogical experiment was organized on the basis of the school of aerial gymnastics and sports on the pylon "Noon" (Ulyanovsk), girls aged 12-14 years old took part in it (experience in pole sports - three to four years). Results and conclusions. Effective means and methods of acrobatic training in pylon sports at the stage of sports specialization have been determined, a methodology for complex special acrobatic training has been developed to improve the quality of performance of stunt and near-pylon acrobatic exercises in competitive compositions of pylon sports by female athletes aged 12-14, taking into account the specifics of the content of competitive activity. At the end of the work, the selection of acrobatic training means was performed based on the structural correspondence of basic acrobatic exercises to the obligatory trick elements of competitive compositions on the pylon (on the floor), taking into account the specifics of the main loads, the nature of their impact on the articular-ligamentous apparatus of the upper and lower extremities, which causes an increase in quality aspects of competitive programs, their attractiveness.